Relation Between Physical Activities and Built Environment: A Literature Review (Journal of Life and Earth Science, 2014)
Physical inactivity has been a leading factor of chronic diseases and high rate of mortality in the world. Despite the fact, only a small portion of people are able to meet up the recommended physical activities. However, there are handful studies suggest that built environment may provide stimulus or barriers to peoples participation in physical activities. Drawing upon this context, this paper aims to review articles regarding built environment and physical activity focusing on characteristics of built environment which are particularly helpful in improving neighborhood environment, and to catch the attention to physical activities, such as walking, and cycling. It also critically reviews the measures of built environment, and finds three measures viz. (i) perceived environment measures, (ii) observational measures, and (iii) GIS-based measures. The article argues that integrated measures of built environment might be helpful to reduce limitations of individual measures and to understand the reasons of less participation in physical activities. It also suggests some practical interventions for improvement of built environment which is essentially inevitable to persuade physical activities. DOI: http://dx.doi.org/10.3329/jles.v7i0.20127 J. Life Earth Sci., Vol. 7: 91-98, 2012